2015
DOI: 10.1155/2015/562586
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use for Public Health Campaigning in a Low Resource Setting: The Case of Waterpipe Tobacco Smoking

Abstract: Introduction. Waterpipe tobacco smoking prevalence is increasing worldwide despite its documented health effects. A general belief that it is less harmful than cigarettes may be fuelled by the lack of media campaigns highlighting its health effects. We aimed to create and assess the impact of a social media campaign about dangers of waterpipe smoking. Methods. The “ShishAware” campaign included three social media (Facebook, Twitter, and YouTube) and a website. Nine months after launch we collected data to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…For example, a shisha campaign had 563 followers over 9 months after disseminating 373 tweets [31], and the Mayo Clinic account had 1,235 followers over 12 months after generating 1,635 tweets [32]. Our results show that the number of followers is critical to reach.…”
Section: Discussionmentioning
confidence: 92%
“…For example, a shisha campaign had 563 followers over 9 months after disseminating 373 tweets [31], and the Mayo Clinic account had 1,235 followers over 12 months after generating 1,635 tweets [32]. Our results show that the number of followers is critical to reach.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, in using Facebook as a medium for health information dissemination, there needs to be some moderation of the content that is posted online. There has been recent research demonstrating how social media use could help in public health campaigning, especially in a low-resource setting [ 40 ]. The authors have reported how effective such media are, given that they have inherent potential for rapid transfer of information to the masses [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that while Facebook attracted campaign supporters, YouTube attracted opposers and concluded that a more detailed evaluation particularly among adolescents is needed. 30 To the best of our knowledge there are few dedicated shisha cessation services in England. Shisha users view their habit very differently to how cigarette smokers view their habit.…”
Section: Effective Cessation Interventionsmentioning
confidence: 99%